SERS-Tags: Selective Immobilization and Detection of Bacteria by Strain-Specific Antibodies and Surface-Enhanced Raman Scattering - Benešová, Markéta; Bernatová, Silvie; Mika, Filip; Pokorná, Zuzana; Ježek, Jan; Šiler, Martin; Samek, Ota; Růžička, Filip; Rebrošová, Katarina; Zemánek, Pavel; Pilát, Zdeněk (Biosensors, 2023)
Efficient separation and sensitive identification of pathogenic bacterial strains is essential for a prosperous modern society, with direct applications in medical diagnostics, drug discovery, biodefense, and food safety. We developed a fast and reliable method for antibody-based selective immobilization of bacteria from suspension onto a gold-plated glass surface, followed by detection using strain-specific antibodies linked to gold nanoparticles decorated with a reporter molecule. The reporter molecules are subsequently detected by surface-enhanced Raman spectroscopy (SERS). Such a multi-functionalized nanoparticle is called a SERS-tag. The presented procedure uses widely accessible and cheap materials for manufacturing and functionalization of the nanoparticles and the immobilization surfaces. Here, we exemplify the use of the produced SERS-tags for sensitive single-cell detection of opportunistic pathogen Escherichia coli, and we demonstrate the selectivity of our method using two other bacterial strains, Staphylococcus aureus and Serratia marcescens, as negative controls. We believe that the described approach has a potential to inspire the development of novel medical diagnostic tools for rapid identification of bacterial pathogens.
Keywords: Spectrum Analysis, Raman; single-cell detection; Ramanova spektroskopie; kovové nanočástice; protilátky; Antibodies; Metal Nanoparticles; Gold; SERS-tag; zlato; Escherichia coli; Staphylococcus aureus; sandwich immunoassay